Analysis of Kegel Gymnastics and Lavender Aromatherapy on Perineal Wound Pain Intensity in Post Partum Mothers, Bujel Village, Mojoroto District, Kediri City - Desi Rahmawati; Desi Setiyawati (PT. Griya Eka Sejahtera, 2022)
Background: A number of the efforts that have been done for reduce pain in mother postpartum with perineal laceration can done by pharmacological and non-pharmacological. However use by pharmacology often cause effect side and sometimes no own strength effects. This study aimed to analyze the effect of Kegel exercises and lavender aromatherapy on the intensity of perineal wound pain in postpartum mothers.Methods: This research is a pre-experimental. The population in this study were all postpartum mothers at PMB Novitasari, Amd., Keb as many as 39 postpartum mothers for the period October 2019-31 January 2020. The sample in this study was all postpartum mothers at PMB Novitasari, Amd., Keb with simple sampling technique. Random Sampling. The test used is Chi-Square.Results: results showed that most (63.9%) of the respondents had pain intensity in the severe category before being given Kegel exercises and lavender aromatherapy, namely 23 people and almost half (47.2%) of the respondents had moderate pain intensity after being given Kegel exercises and lavender aromatherapy, namely 17 people.Conclusion: effect of giving Kegel exercises and lavender aromatherapy on the intensity of pain in pregnant women, while in this study there was a negative rank of 27 which means pain intensity. after being given kegel exercises and lavender aromatherapy decreased compared to pain intensity before being given kegel exercises and lavender aromatherapy